2017
DOI: 10.1111/apt.14401
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: the significance of histological disease severity in lean patients with nonalcoholic fatty liver disease

Abstract: Lean-NAFLD patients tend to show less severe histological features as compared to overweight/obese-NAFLD patients. Subsequent longitudinal assessment is needed to understand the clinical impact of these findings; however, the significant ~ 25% increment of mean fibrosis score in overweight/obese patients suggests that obesity could predict a worse long-term prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 35 publications
3
82
1
Order By: Relevance
“…Recent data showed the presence of NAFLD also in patients with normal BMI, defining the new concept of lean NAFLD . Some studies indicated that lean NAFLD had lower steatosis grade and fibrosis stage compared with overweight or obese NAFLD . On the contrary, lean NAFLD was reported to acquire higher risk of DM, HTN or MetS, increasing the risk of cardiovascular disease .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data showed the presence of NAFLD also in patients with normal BMI, defining the new concept of lean NAFLD . Some studies indicated that lean NAFLD had lower steatosis grade and fibrosis stage compared with overweight or obese NAFLD . On the contrary, lean NAFLD was reported to acquire higher risk of DM, HTN or MetS, increasing the risk of cardiovascular disease .…”
Section: Discussionmentioning
confidence: 99%
“…28 Some studies indicated that lean NAFLD had lower steatosis grade and fibrosis stage compared with overweight or obese NAFLD. 29 On the contrary, lean NAFLD was reported to acquire higher risk of DM, HTN or MetS, increasing the risk of cardiovascular disease. 30 32 the association between MetS and HCV infection could not be clearly identified without the data of HCV genotype.…”
Section: Factors Associated With Metabolic Syndrome In Lean Body Sumentioning
confidence: 99%
“…4 NAFLD can also appear in non-obese subjects. 5,6 Many studies have described the deleterious effects of NAFLD, which range from liver damage to increased risk of cardiovascular 7,8 or kidney disease. 9 Despite NAFLD shares common risk factors with cardiovascular and chronic kidney disease, they seem to play an additional role in the pathogenesis of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Although new and efficient drugs that can safely cure hepatitis C with high rates of sustained virological response have been developed, fibrosis still progresses in some patients with a further risk of cirrhosis and HCC development, mainly in those with advanced fibrosis . Recently, liver steatosis has been described as an additional risk factor for fibrosis progression and HCC development in patients with and without hepatitis C . Hepatic steatosis is defined as excessive fat accumulation in the liver.…”
Section: Introductionmentioning
confidence: 99%